Mechanical Properties of Additively Manufactured Polymeric Materials—PLA and PETG—For Biomechanical Applications - Martins, Rui F. (2024)
GDA\u0143SK TECH CORE EDU FACILITIES, grant no. 23/2021/EDU, Laboratory of Additive Manufacturing Methods and Reverse Engineering. Publisher Copyright: © 2024 by the authors.